2017
DOI: 10.1007/s00436-017-5722-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of five essential oils against Pediculus humanus capitis

Abstract: Treatment of head lice has relied mainly on the use of topical insecticides. Today, conventional topical pediculicides have suffered considerable loss of activity worldwide. There is increasing interest in the use of natural products such as essential oils for head louse control, and many of them are now incorporated into various over-the-counter products presented as pediculicides, often without proper evaluation. The aim of the present study was to assess the in vitro efficacy of five essential oils against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 27 publications
0
38
0
1
Order By: Relevance
“…In addition, ivermectin is the only drug currently used for oral treatment, and its highly effectiveness was clinically approved for both louse ecotypes treatment (Foucault et al, 2006;Chosidow et al, 2010), although empirically noted ivermectin resistance has started to be reported in the field in Senegal (Diatta et al, 2016). There is also growing interest in the use of natural products such as pediculicides based on plant-derived essential oils (eucalyptus oil and tea tree oil) or with a purely physical mode of action, such as dimeticone and benzyl alcohol (Meinking et al, 2010;Burgess et al, 2013;Candy et al, 2018b), but little attention has been given to their clinical evaluation for effectiveness, even though some of them are already commercialized.…”
Section: Control Of Lice Infestations and Evolution Of Insecticide Rementioning
confidence: 99%
“…In addition, ivermectin is the only drug currently used for oral treatment, and its highly effectiveness was clinically approved for both louse ecotypes treatment (Foucault et al, 2006;Chosidow et al, 2010), although empirically noted ivermectin resistance has started to be reported in the field in Senegal (Diatta et al, 2016). There is also growing interest in the use of natural products such as pediculicides based on plant-derived essential oils (eucalyptus oil and tea tree oil) or with a purely physical mode of action, such as dimeticone and benzyl alcohol (Meinking et al, 2010;Burgess et al, 2013;Candy et al, 2018b), but little attention has been given to their clinical evaluation for effectiveness, even though some of them are already commercialized.…”
Section: Control Of Lice Infestations and Evolution Of Insecticide Rementioning
confidence: 99%
“…Tea tree oil was reported to be potentially effective against both head and body lice [52,54,55]. The main components of M. alternifolia are terpinen-4-ol, γ-terpinene, α-terpinene, and α-terpineol [56].…”
Section: Melaleucamentioning
confidence: 99%
“…The dried flower of clove is a popular kitchen spice used in both food and ▶ PH: Pediculus humanus medicine (anesthetic, analgesic, antimicrobial, antioxidant, antiinflammatory, and anticancer agents) [61]. E. caryophyllata (clove oil) was reported to display high pediculicidal activity against head lice [40,56], which was comparable to that of commercial insecticides d-phenothrin and pyrethrum [62]. In addition, clove oil and its major component (eugenol) have repellant, acaricidal, and insecticidal activities (against Aedes and Anopheles mosquitoes, D. gallinae, and Sarcoptes scabiei) [29,63].…”
Section: Eugeniamentioning
confidence: 99%
See 1 more Smart Citation
“…It abounds in warm and dry conditions (Manivannan, 2015). There are various reports of the fumigant and repellent activities of essential oils on T. castaneum (Stefanazzi, Stadler, & Ferrero, 2011;Jaramillo-Colorado, Martelo, & Duarte, 2012;Taban, Saharkhiz, & Hooshmandi, 2017;Candy, Nicolas, Andriantsoanirina, Izri, & Durand, 2018;Hu, Wang, & Dai, 2019). However, there are no reports on B. graveolens and its components.…”
Section: Introductionmentioning
confidence: 99%